Math for business and finance an algebraic approach - Slater, Jeffrey; Wittry, Sharon M. (The McGraw-Hill/Irwin series in operations and decision sciences, 2019)
Math for Business & Finance: An Algebraic Approach provides modern examples for students to understand business mathematics and make connections with real-world applications. The course covers mathematical concepts from an algebraic approach, combined with Business applications. Every chapter is devoted to a Personal Finance theme, with topics that include Payroll and the Cost of Purchasing a Home. There is also extensive integration of scientific calculator notation, and also has the Wall Street Journal and Kiplinger news clips that have been widely popular in Jeffrey Slater's other two Business Math texts. Connect is the only integrated learning system that empowers students by continuously adapting to deliver precisely what they need, when they need it, and how they need it, so that your class time is more engaging and effective.